Survival of acid adapted and non-acid adapted Salmonella Typhimurium in pasteurized orange juice and yogurt under different storage temperatures. (October 2013) - Álvarez-Ordóñez, Avelino; Valdés, Lorena; Bernardo, Ana; Prieto, Miguel; López, Mercedes
The survival capacity of Salmonella enterica serovar Typhimurium acid adapted and non-acid adapted cells was monitored in pasteurized yogurt (pH 4.1) and orange juice (pH 3.6) during storage at different temperatures (4, 10, 25 and 37 ℃). Acid adapted and non-acid adapted cells were obtained by means of their growth for 36 h in Brain Heart Infusion broth acidified at pH 4.8 with citric acid and buffered (pH 7.0) Brain Heart Infusion broth, respectively. S. typhimurium showed a great ability to survive in both foodstuffs and, especially, in yogurt, where both acid adapted and non-acid adapted populations suffered only a reduction of about 1.3–1.9 log10 cycles after 43 days of storage in the range of temperatures 4–25 ℃. At 37 ℃ a higher bacterial inactivation was observed (4.0–4.4 log10 cycles). In orange juice, a different behaviour was observed for acid-adapted and non-acid adapted cells. Whereas non-acid adapted cells survived better than acid adapted cells at 4 and 10 ℃, acid adapted cells showed enhanced survival abilities at higher temperatures (25 and 37 ℃). Thus, the times required to achieve a 5 log10 cycles reduction for non-acid adapted and acid adapted cells were 10.2 and 6.0 (4 ℃), 6.3 and 4.2 (10 ℃), 0.6 and 1.0 (25 ℃) and 0.10 and 0.15 (37 ℃) days, respectively. Evidence found in this study demonstrates that refrigeration temperatures protect S. typhimurium from inactivation in acid foods and indicates that S. typhimurium acid tolerance response (ATR) is determined by storage temperature and food composition.